Imagination Cannot Generate Empirical Justification or Knowledge. - Egeland, Jonathan (Erkenntnis, 2025)
What is the epistemic function of imagination? Traditionally, philosophers have claimed that the epistemic function of imagination is exhausted by its ability to provide justification for modal beliefs, or that it is epistemically irrelevant. However, in recent years a number of philosophers have broken with the tradition by arguing that imagination can generate justification or knowledge about contingent empirical facts. This paper argues against this view by developing a new dilemma. The upshot of the argument is that although imagination does have an important epistemic function that has evaded the traditional view, it cannot give rise to new empirical justification or knowledge.